2023
DOI: 10.1111/aec.13330
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fish assemblage as seed dispersers in Amazon oligotrophic flooded forests

Abstract: In tropical and highly diverse systems, Seed Dispersal Effectiveness (SDE) is a very useful approach to investigating the role of seed dispersers in one of the most important and complex phases of plants by analysing the quantitative (QC) and qualitative (QL) components of the seed dispersal process. Although fishes are recognized as an important guild of frugivores in flooded environments, we still know very little about the dispersal effectiveness performed by this group. Our study evaluated two quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…Specialisation or generalisation of interactions are commonly characterised as the number of partners and, in general, there are two levels of specialisation measures: first, the characterisation of focal species (d′) and, second, the degree of specialisation of an entire interaction network (H 2 ′) (Blüthgen et al., 2006). In flooded forests, specialist or generalist habits can influence the effectiveness of frugivorous fish in seed dispersal (Weiss et al., 2023). While generalist species tend to interact with a greater number of plants than specialist species (Correa et al., 2016), specialist species are fundamental in the organisation and connection of modules within the network (Olesen et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specialisation or generalisation of interactions are commonly characterised as the number of partners and, in general, there are two levels of specialisation measures: first, the characterisation of focal species (d′) and, second, the degree of specialisation of an entire interaction network (H 2 ′) (Blüthgen et al., 2006). In flooded forests, specialist or generalist habits can influence the effectiveness of frugivorous fish in seed dispersal (Weiss et al., 2023). While generalist species tend to interact with a greater number of plants than specialist species (Correa et al., 2016), specialist species are fundamental in the organisation and connection of modules within the network (Olesen et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moving from temperate grasslands to Amazonian flooded forests, Weiss et al (2024) evaluated the effectiveness of fish as seed dispersers. They studied both quantity and viability of seeds ingested by fish and found that fish that feed on fruits and seeds are more effective seed dispersers compared to generalists.…”
mentioning
confidence: 99%